Euro area sovereign yields and the power of QE - Afonso, António (2017)
We assess the determinants of long-term sovereign yield spreads using a panel of 10 Euro area countries over the period 1999.01–2016.07 notably regarding the ECB (standard and non-standard) quantitative easing measures. Our findings indicate that the international risk, the bid-ask spread and real effective exchange rate increased the 10-year sovereign bond yield spreads. Moreover, quantitative easing, notably Longer-term Refinancing Operations (LTROs), Targeted LTROs and the Securities Market Program decreased the yield spreads.